Perilaku Hidup Bersih dan Sehat Serta Pemberian Makanan Sehat Pada Anak Sekolah Dasar - Laura B. S. Huwae; Johan B. Bension; Revi A. Rumbawa; Fira A. Rehalat; Kuntum N. Lisaholet; Laury M. Ch. Huwae; Ronald D. Hukubun (Jurnal Pengabdian Bidang Kesehatan, 2024)
This study focuses on clean and healthy living behavior (PHBS) and the provision of healthy food to elementary school children. The aim is to enhance PHBS habits and healthy food intake among students through a participatory approach involving students, teachers, and parents. The research method includes sosialitation and interviews, with subjects being third to 4 and 5 students in elementary schools in 56 Perumnas Poka. Results show significant improvements in personal hygiene habits, the use of sanitation facilities, and the purchase and consumption of healthy food at school. Involvement teachers support also increased, contributing to the program's success. Positive feedback was received from the school community, though challenges such as resource limitations and the need for consistent monitoring remain. This study highlights the importance of community collaboration in promoting children's health.